2018
DOI: 10.1017/s0954579418001116
|View full text |Cite
|
Sign up to set email alerts
|

The role of bicultural adaptation, familism, and family conflict in Mexican American adolescents’ cortisol reactivity

Abstract: Scarce research has examined stress responsivity among Latino youths, and no studies have focused on the role of acculturation in shaping cortisol stress response in this population. This study assessed Mexican American adolescents’ Mexican and Anglo cultural orientations and examined prospective associations between their patterns of bicultural orientation and hypothalamic–pituitary–adrenal cortisol reactivity to an adapted Trier Social Stress Test. The sample included 264 youths from a longitudinal birth coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 157 publications
(211 reference statements)
0
18
0
Order By: Relevance
“…Thus, the lack of support for this model from the present review is likely more indicative of a gap in the literature rather than evidence that these relations do not exist. Consistent with stress and coping theory, several studies showed that the balance of cultural stressors and resources mattered when considering implications for stress biology (Gonzales, Johnson, et al, 2018; Miles et al., 2018; Zeiders et al., 2018). Taken together, these studies suggest that stress biology may modulate or serve as a pathway by which cultural constructs influence immigrant youth adjustment, although more work is needed to investigate the links between stress biology and specific outcomes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Thus, the lack of support for this model from the present review is likely more indicative of a gap in the literature rather than evidence that these relations do not exist. Consistent with stress and coping theory, several studies showed that the balance of cultural stressors and resources mattered when considering implications for stress biology (Gonzales, Johnson, et al, 2018; Miles et al., 2018; Zeiders et al., 2018). Taken together, these studies suggest that stress biology may modulate or serve as a pathway by which cultural constructs influence immigrant youth adjustment, although more work is needed to investigate the links between stress biology and specific outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…While acculturation is also typically discussed as a risk factor, biculturalism and ERI affirmation are promising as promotive factors for acculturating adolescents, and their positive effects on adjustment may be transmitted through stress biology. Interestingly, two studies found no associations between reported familism values and HPA axis functioning (Doane et al., 2018; Gonzales, Johnson, et al, 2018). However, one of these studies (Doane et al., 2018) did find that specific beliefs and practices associated with familism , such as family assistance behaviors, showed meaningful associations with cortisol.…”
Section: Methodsmentioning
confidence: 99%
“…Familism values may operate in a protective fashion by espousing the provision of economic and emotional support to family members and a sense of loyalty and respect within family relations (Germán, Gonzales, & Dumka, 2008). Illustratively, bicultural adolescents who endorse high orientation to both Anglo and Mexican orientation have been shown to exhibit a stronger, more adaptive cortisol response to a laboratory stressor compared to adolescents who endorsed high levels of Anglo orientation only (Gonzales et al, 2018). Similar values emphasize the primacy of family/ social ties that exist in other cultural contexts (e.g., communalism among African Americans and filial piety among Asian Americans) and may also operate to buffer minority individuals from the negative consequences of physiological stress response systems that are chronically activated by discriminatory practices, racism, neighborhood violence, and other daily stressors disproportionally experienced by individuals of nonmajority culture groups (Doane et al, 2018).…”
Section: Biological Resilience In a Culturally Sensitive Frameworkmentioning
confidence: 99%
“…Thus, ethnic-racial identity content may function as a cultural protective factor linked to lower depressive symptoms among Latino adolescents. Gonzales, Johnson, et al (2018) studied the role of bicultural adaptation, familism, and family conflict in Mexican American adolescents' cortisol reactivity. They assessed Mexican and Anglo cultural orientations, prospective associations between their patterns of bicultural orientation, and hypothalamic-pituitary-adrenal axis cortisol reactivity to an adapted Trier Social Stress Test in a sample 264 Mexican American adolescents at ages 12 and 14.…”
Section: Equifinality and Multifinality In Cultural Developmentmentioning
confidence: 99%